Engaging students using social media: The students' perspective. (May 2015) - Al-Bahrani, Abdullah; Patel, Darshak; Sheridan, Brandon
Abstract: Social media access and usage has grown rapidly in the past several years. In academia, social media is a new pedagogical tool that may be used to engage students both inside and outside the economics classroom, and impact their overall success. In this study we examine the students' view of incorporating social media in the classroom. The survey was administered at three academic institutions. The results are based on a survey administered to students in Principles of Microeconomics and Macroeconomics courses. Students have the strongest presence, in descending order, on Facebook, YouTube, Instagram, and Twitter. However, based on their utilization preferences, these mediums are ranked as follows: Instagram, Facebook, Twitter and YouTube. The results indicate that students are concerned with privacy but are more willing to connect with faculty if the connection is "one-way" and participate if social media is a voluntary part of class. Therefore Twitter, YouTube and Instagram, or Facebook "like" pages or groups are potentially better mediums for faculty to use in economic classrooms. The survey indicates that students use their social media accounts more frequently than email or Learning Management Systems and, therefore, social media may also be a more effective tool for spontaneous communication for many students.